RESEARCH OF PARAMETERS PRISMATIC PLACEHOLDER WITH THE STATIC LOADING - O. M. Ustarkhanov; М. S. Alibekov; T. O. Ustarkhanov (Вестник Дагестанского государственного технического университета: Технические науки)
The work is devoted to experimental research of parameters of prismatic aggregate at static loading. The data of experimental researches allow to use them in the design of three-layer structures in space, aviation techniques, as well as in construction and machinery that is of interest for technical workers and designers.